THE INFLUENCE OF PRINCIPAL LEADERSHIP AND WORK MOTIVATION ON TEACHER PROFESSIONALISM AT MADRASAH ALIYAH ULUL ALBAB LUBUKLINGGAU - Devi Sartika; Jumira Warlizasusi; Saidil Mustar; Elce Purwandari (STAI Ma'had Aly Al-Hikam Malang, 2023)
Principal leadership is a leader's behavior pattern when directing and controlling his subordinates to follow his will in achieving goals. The next important element in the world of education is the teacher. Teachers are an important part of the education system, especially in schools. The purpose of this study was to determine the influence of the principal's leadership and work motivation on teacher professionalism at Madrasah Aliyah Ulul Albab Lubuklinggau. The method used in this research is quantitative. The research subjects were teachers at Madrasah Aliyah Ulul Albab Lubuklinggau. The sample in the study consisted of 40 teachers. Data collection techniques using a questionnaire. Descriptive analysis and inferential analysis were used for data analysis. The results of the study show that: (1) Principal leadership has a positive effect on teacher professionalism at 68.2%. (2) There is a positive and significant influence between the principal's work motivation on teacher professionalism of 69.8%. (3) There is a mutual influence between the principal's leadership and work motivation on teacher professionalism of 86.9%. The r value is smaller than the level used, namely 0.000 or 0.000 <0.05 so that Ho is rejected and Ha is accepted.